Medical students’ exposure to and attitudes towards product promotion and incentives from the pharmaceutical industry in 2019: a national cross-sectional study in France - Maxime Esvan; Benjamin Bastian; Martin Molina; Adeline Boëffard (BMJ Open)
Objectives To measure medical students’ exposure to pharmaceutical product promotion and incentives nationwide, and to evaluate students’ attitudes towards the pharmaceutical industry, access to education on promotional strategies and knowledge of institutional policies about drug company-student relationships.Design Cross-sectional survey based on a 48-item anonymous questionnaire.Setting All 37 French medical schools, from March to April 2019.Participants French medical students in their 4th year of study and beyond, having studied exclusively in France.Main outcome measure Cumulative frequency of students’ exposure to pharmaceutical product promotion and incentives.Secondary outcome measures Exposure within the last 6 months, attitudes regarding interactions with the industry, access to education on pharmaceutical product promotion and incentives and knowledge of institutional policies.Results 6280 responses were analysed (10.4% out of a total of 60 550 eligible students). 5992 students (96.3% poststratification, 99% CI (96.1% to 96.5%)) had already been exposed to pharmaceutical product promotion and incentives and 4650 (78.1%, 99% CI (77.7% to 78.6%)) within the last 6 months. 5140 students (85.4%, 99% CI (84.8% to 85.8%)) had met a pharmaceutical representative. Regarding attitudes, 2195 students (36.8%, 99% CI (36.0% to 37.5%)) thought receiving a gift could influence their own prescriptions while 3252 (53.6%, 99% CI (53.1% to 54.2%)) thought it could influence their colleagues’ prescriptions. 4533 students (76.0%, 99% CI (75.6% to 76.5%)) reported never having attended any lecture on promotional strategies. Exposure seemed to depend on the year of study and specialty. 5122 (88.1%, 99% CI (87.7% to 88.4%)) did not know whether their faculty had a policy regarding drug company-student interactions.Conclusion In France in 2019, medical students’ exposure to pharmaceutical product promotion and incentives remains considerable and starts early during medical training. Education on promotional strategies and institutional policies should be improved to ensure responsible and ethical behaviour in prescribing medications.